New Higgs interactions in ZZ gamma and Z gamma gamma production - Lietti, S. M. [UNESP]; Novaes, Sérgio Ferraz [UNESP] (Elsevier B.V., 1998)
The effect of new operators that only modify the bosonic couplings of the Higgs boson, without altering the WW gamma or WWZ three-point functions, are examined in the e(+)e(-) --> ZZ gamma and Z gamma gamma processes. We analyse the constraints on these interactions that can be imposed by the LEP II collider at CERN and at the Next Linear Collider. (C) 1998 Elsevier B.V. B.V.